Investigating the Role of Friendship Interventions on the Mental Health Outcomes of Adolescents: A Scoping Review of Range and A Systematic Review of Effectiveness - Tanya Manchanda; Alan Stein and Mina Fazel (My University, 2023)
Friendships are crucial in adolescent development. This paper presents a scoping review, followed by a systematic review, to assess friendship interventions and their impacts on the mental health outcomes of adolescents aged 12–24 years. Studies were included if they incorporated a friend or authentic social group in an intervention dedicated to improving mental health outcomes and well‐being. Twenty‐four studies were included in the scoping review, and eighteen in the sys‐ tematic review. Data from 12,815 adolescents were analysed; three prominent themes emerged. The most common theme was promoting mental health literacy, followed by supporting help‐seeking, and friendship‐building/combating isolation. Most evaluations focused on the individual who had received the intervention, rather than their wider friends who would have been potential contacts and experienced any altered interactions. Of the studies focusing on friendship‐building, all had positive short‐term outcomes but inconclusive long‐term effects. Two studies recruited friends from an individual’s authentic social group. While opportunities for improving mental health literacy and help‐seeking emerged as key themes, the role of friends in mental health interventions has only been included in a small number of studies. Given that friends are a key point of contact for many adolescents, a better understanding of their domains of influence, particularly on mental health, will potentially enhance interventions.
Keywords: : friendship; mental health; adolescents; intervention; help‐seeking